2021
DOI: 10.1186/s13104-021-05707-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring health workers’ experiences of mental health challenges during care of patients with COVID-19 in Uganda: a qualitative study

Abstract: Objectives The aim of this study is to qualitatively investigate the lived experiences of mental health among frontline health workers providing COVID-19-realted care in Uganda. This study provides insights into the contextual realities of the mental health of health workers facing greater challenges given the lack of adequate resources, facilities and health workers to meet the demand brought about by COVID-19. Results All in all, our findings sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(126 citation statements)
references
References 9 publications
4
116
0
Order By: Relevance
“…Moreover, sex, age, marital status, type of profession, and working environment were signi cant factors for PTSD symptoms [37,41]. However, one study in Ethiopia found that the odds of depression were twice as high among male healthcare providers than among female healthcare providers [35].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sex, age, marital status, type of profession, and working environment were signi cant factors for PTSD symptoms [37,41]. However, one study in Ethiopia found that the odds of depression were twice as high among male healthcare providers than among female healthcare providers [35].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The 12 studies included in this review consisted of 11 cross-sectional quantitative and 01 qualitative studies. The most typical mental health conditions assessed in the literature were: depression, anxiety, perceived Stress, post-traumatic stress disorders (PTSD), coping strategy, perceived health status, health distress (including burnout), insomnia, and perceived stigma [35,36].…”
Section: Study Characteristicsmentioning
confidence: 99%
“… 3 In Uganda, the health worker density is only 0.71 indicating a huge shortage in care. 4 Such a dilemma coupled with other diseases like HIV, malaria, and lower respiratory infections have put the healthcare system in the country at greater risk of collapse. 4 The onset of the second wave of COVID-19 poses an even greater threat on the healthcare system particularly the frontline nurses providing direct care to COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies indicated that health workers were under serious psychological stress as a result of COVID-19. 4 , 6 Remarkably, little is known about the burden of PTSD and its predictive factors among nurses in Uganda during the COVID-19 pandemic. Therefore, the current study assessed the prevalence and predictive factors of PTSD in nurses during COVID-19 in central Uganda.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation